ANALISIS VARIABEL MONETER AMERIKA SERIKAT TERHADAP PERTUMBUHAN EKONOMI NEGARA EMERGING MARKET - Sindi Oktaviani; Hasdi Aimon; Dewi Zaini Putri (Universitas Negeri Padang, 2019)
This study aims to find effect of monetary variable of US on economic growth in emerging market countries, such as Indonesian, Malaysian, Thailand and Philipines. These four countries are commonly called tiger cub countries that have the potential to become developed countriesin the future. The data used are secondary data in the form of time series from 2010:Q1 until 2018:Q4. The variables used are gap of The Fed Funds rate and gap of Inflation of US as exogen variable. Then, exchange rate and economic growth as endogen variable. The research methods used are simultaneous equation regression model with indirect least square methode. The results of the study show that (1)Gap of The Fed Interest Rate has a significant effect on the exchange rate in all sample of Emerging Market Countries while US inflation only has a significant effect on the exchange rate in Indonesia.(2) in simultaneously gap of The Fed Interest rate, gap of US inflation and the exchange rate which contaminated by changes in the US monetary variable have a significant influence on economic growth in Emerging Market Countries, except in Malaysian.(3) In partially, gap of The Fed Interest rate and the exchange rate have a significant influence on economic growth in Indonesian, Thailand and Philipines.While gap of US inflation has a significant influence on economic growth only in Indonesian and Philipines.